2004
DOI: 10.1111/j.1440-1827.2004.01590.x
|View full text |Cite
|
Sign up to set email alerts
|

Invasive micropapillary carcinoma of the breast: Clinicopathological and immunohistochemical study

Abstract: Invasive micropapillary carcinoma (IMPCa) of the breast refers to a unique variant of invasive ductal carcinoma, but its biological behavior has not been elucidated well. We analyzed 16 IMPCa cases (10 pure type, six mixed type). The incidence of IMPCa was 1.0% of all primary breast carcinoma. High nuclear grade (75.0%), as well as poorly differentiated histological grade (81.3%), was frequently seen. Lymph node metastases were evident in 92.9% of the examined cases, and about half of them showed more than 10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
38
0
6

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(53 citation statements)
references
References 11 publications
9
38
0
6
Order By: Relevance
“…Characteristics observed in this report such as low cell proliferation index, positivity for hormone receptors, and negativity for HER-2 are related to better prognosis in humans (Pinder et al 1995;Onitilo et al 2009). However, metastasis to all lymph nodes was observed, supporting the described lymphatic dissemination in humans (Luna-more´et al 1994;De la Cruz et al 2004), dogs (Cassali et al 2002), and cats (Seixas et al 2007).…”
supporting
confidence: 76%
“…Characteristics observed in this report such as low cell proliferation index, positivity for hormone receptors, and negativity for HER-2 are related to better prognosis in humans (Pinder et al 1995;Onitilo et al 2009). However, metastasis to all lymph nodes was observed, supporting the described lymphatic dissemination in humans (Luna-more´et al 1994;De la Cruz et al 2004), dogs (Cassali et al 2002), and cats (Seixas et al 2007).…”
supporting
confidence: 76%
“…Bu boşlukların vasküler kökenli olmadığı immünohistokimyasal olarak endotelyal belirteçler (CD31 ve FaktörVIII) ile boyanmamaları ile kanıtlanmıştır (17). İMPK için tanımlayıcı bir özellik olan bu boşluklar fiksasyon artefaktıdır ve frozen kesitlerde bu boşluklar izlenmemektedir (18).…”
Section: Morfoloji̇unclassified
“…Mikropapiller karsinom komponentinin nükleer özellikleri genellikle eşlik eden duktal komponente benzer ve yüksek derecelidir (6)(7)(8)(9)(10)(11). Duktal karsinoma in situ (DKİS) %53-80 oranında görülmekte olup çoğunlukla mikropapiller, kribriform veya papiller tiptedir (1,7,8,18,20).…”
Section: Memeni̇n İnvazi̇v Mi̇kropapi̇ller Karsi̇nomuunclassified
See 1 more Smart Citation
“…In a study based on data collected from 1,056 women with primary breast carcinoma, the incidence of all IMC variants was 11 (1.0%) and that of pure IMC was 6 (0.6%). 2 In a report based on 16 female cats with mammary IMCs, only 1 (6.3%) had a pure micropapillary pattern. 11 In an unrelated dog study, none of the 9 IMCs evaluated showed a pure micropapillary pattern.…”
mentioning
confidence: 99%